To Rethink Standards of Civilisation, Start with the End. (June 2014) - Bowden, Brett
Many people recognise that there is a need to distinguish between states in the international system, such as on the basis of legitimacy. For much of the system's history the means of drawing such distinctions have been standards of civilisation. For some, the need to divide and separate is unavoidable; others are more critical of standards of civilisation because of the consequences that come with exclusion or the pressure to conform. On both sides it is often downplayed that standards of civilisation are, by and large, a means to an end. If we want to rethink the way standards of civilisation work and mitigate some of their more unsavoury consequences, then we need to rethink the end they are designed to achieve, which is best captured in Kant's title 'Idea for a Universal History from a Cosmopolitan Point of View'.